Atypical Presentation of Idiopathic Bilateral Optic Perineuritis in a Young Patient - Tevaraj, Jessica Mani Penny; Tai, Evelyn Li Min; Mohd Noor, Raja Azmi; Thavaratnam, Lakana Kumar; Win Mar, Salmah; Wan Hitam, Wan Hazabbah (Hindawi Publishing Corporation, 2016)
A previously healthy 27-year-oldMalay male presented with acute onset of painless, severe blurring of vision in his right eye. It was associated with headache and vomiting for the pastweek. Relative afferent pupillary defectwas present in the right eye,with reduced optic nerve function. Patient also had bilateral generalised optic disc swelling, splinter haemorrhages, and tortuous vessels. Initial examination was suggestive of either optic neuritis or raised intracranial pressure. Typical features of bilateral optic perineuritis (OPN) such as tram track and doughnut sign were observed on magnetic resonance imaging. Connective tissue and infective screening were negative. He was diagnosed with bilateral optic perineuritis and treated with high dose intravenous corticosteroids followed by a three-month course of oral steroids. His vision and optic nerve function recovered to baseline levels.